Erratum: Experimentally observed evolution between dynamic patterns and intrinsic localized modes in a driven nonlinear electrical cyclic lattice. (7th June 2019) - Shige, S.; Miyasaka, K.; Shi, W.; Soga, Y.; Sato, M.; Sievers, A. J.
Abstract: Original article: EPL, 121 (2018) 30003 .